ANALYSIS OF NON JUDGE MEDIATORS' EFFORTS IN THE SETTLEMENT OF CIVIL CASES BASED ON PERMA NUMBER 1 YEAR 2016 CONCERNING MEDIATION PROCEDURES - Muhammad Syaifudin Amin; Baharudin Baharudin; Yulia Hesti (Law Faculty of Universitas Bandar Lampung, 2022)
Mediation is one of the faster and cheaper dispute resolution processes, and can provide greater access to justice for the parties in finding a satisfactory dispute resolution and fulfilling a sense of justice. case in court. The problems in this research are the efforts of non-judge mediators in settling civil cases based on PERMA Number 1 of 2016 and the inhibiting factors of non-judge mediators in settling civil cases based on PERMA Number 1 of 2016. The results of the study, Non-Judge Mediators Efforts in Settlement of Civil Cases Based on PERMA Number 1 of 2016 that mediation is a controlled process, where a neutral and objective party can be accepted by both parties to the dispute, helping the parties to find an agreement that can be accepted by the parties. both to end the dispute between them. inhibiting factors of non-judge mediators in the settlement of civil cases Based on PERMA Number 1 of 2016 that the parties are not in good faith, the parties are supported by their environment, good faith is one of the factors that most influence the success of mediation because the parties are the main actors in the mediation process, whatever What happens during the mediation process is the responsibility of the parties to determine their own desires, the mediator only directs and helps provide choices, not to make decisions on what the parties want.